Evaluation of Antimicrobial and Antibiofilm Effects of Almond (Prunus amygdalus) Green Skin Extract on Pseudomonas aeruginosa and Staphylococcus aureus Isolates - Fatemeh Keshavarz; Shima Gharibi; Farkhondeh Poursina; Hamed Fakhim (Canadian Journal of Infectious Diseases and Medical Microbiology)
Conclusion: The combination of antibiotics with almond green skin extract enhances bactericidal and antibiofilm properties against clinical isolates of S. aureus and P. aeruginosa.